ANALISIS EFISIENSI BIAYA DENGAN MENGGUNAKAN METODE TRANSPORTASI PADA PENDISTRIBUSIAN BARANG PT. XYZ - Prihandoko, Danang; Elvina, Elvina; Hartono, Dedy (Banking & Management Review, 2021)
This research purpose is to streamline the cost of PT. XYZ goods shipping. The company will know the cost efficiency between using the third party transportation services or their own transportation. This reseacrh method is descriptive, the required data is obtained by conducting a survey at this company. Analysis data in this research are using Transportation Method. To get the optimal shipping cost, company had using transportation services by using Transportation Method with North West Corner (NWC), Least Cost, and Vogel’s Approximation Method (VAM) approaches. And result of this research is indicate that the method of company using on their own transportation is not optimal, and the company can streamline the cost if using third party transportation services rather than using their own transportation to the destination area. To get the optimal cost, company ought to use Transportation Method.